PhICl2 is activated by chloride ions. Issue 34 (11th August 2021) - Tania,; Poynder, Tiffany B.; Kaur, Aishvaryadeep; Barwise, Lachlan; Houston, Sevan D.; Nair, Akshay J.; Clegg, Jack K.; Wilson, David J. D.; Dutton, Jason L.
Abstract : A study on the potential activating role of pyridine in the electrophilic chlorination of anisole by PhICl2 has led to the discovery that soluble sources of chloride ions activate PhICl2 in the reaction at catalytic loadings, greatly increasing the rate of chlorination. Abstract : A study on the potential activating role of pyridine in the electrophilic chlorination of anisole by PhICl2 has led to the discovery that soluble sources of chloride ions activate PhICl2 in the reaction at catalytic loadings, greatly increasing the rate of chlorination. It is further shown that presence of chloride increases the rate of decomposition of PhICl2 into PhI and Cl2 . The specific mechanism by which chloride induces electrophilic chlorination and decomposition of PhICl2 remains an open question.